2020
DOI: 10.21203/rs.3.rs-63444/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between single nucleotide polymorphisms in CDKAL1 and HHEX and type 2 diabetes in Chinese Population

Abstract: Background: Type 2 diabetes mellitus (T2DM) has a high global prevalence, and the interaction of environmental factors and genetic factors may contribute to the risk of T2DM. We aimed to investigate the association between T2DM and the single nucleotide polymorphisms (SNPs) in genes associated with insulin secretion is necessary. Methods: T2DM (1169) and nondiabetic (NDM) (1277) subjects were enrolled and the eight SNPs in CDKAL1 and HHEX associated with insulin secretion were genotyped in a Chinese population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This study identified that the CDKAL1 rs7754840 polymorphism involved in the susceptibility to T2DM (Li et al, 2021), did not contribute to the susceptibility to FDSP in the Chinese population.…”
Section: Discussionmentioning
confidence: 68%
“…This study identified that the CDKAL1 rs7754840 polymorphism involved in the susceptibility to T2DM (Li et al, 2021), did not contribute to the susceptibility to FDSP in the Chinese population.…”
Section: Discussionmentioning
confidence: 68%